Effect of Milsana concentration in metabolism of solanum lycopersicum plants grown under salinity stress - Christoulaki, Maria Eirini (Cranfield University, 2013)
Salinity is a major abiotic factor that causes serious problems in agriculture around the world which leads to reduced crop production. Scientists all over the world are looking for natural, environment friendly compounds against biotic and abiotic factors. Milsana, a formulated plant extract from Reynoutria sachalinensis, is widely used to elicit plant defences against biotic stress. In addition Milsana has been found to act by enhancing the flavonoid metabolic pathway. Considering the about the effect of Milsana concentration on tomato plants under physiological conditions and under NaCl stress was examined. The experimental approach included the study of the effect of various concentrations of Milsana (0/5%, 1.0% and 2.0%) on untreated plants and plants under salinity stress (70mM and 140mM NaCl). Plant height, fruit quality, antioxidant and photosynthetic capacity were used to determine the response of tomato plants to Milsana, NaCl stress, and their combination. The effect of Milsana was tested in two different sets of experiments, one carried out in growth chambers under controlled conditions and the other carried out in a greenhouse. Milsana led to enhanced growth, when applied to non saline stressed plants. Furthermore the negative effect of NaC1 on photosynthesis, ROS homeostasis, and fruit quality traits was counteracted by the application of Milsana.